2005
DOI: 10.1002/chin.200528031
|View full text |Cite
|
Sign up to set email alerts
|

Nucleophilic Acyl Substitutions of Anhydrides with Protic Nucleophiles Catalyzed by Amphoteric, Oxomolybdenum Species.

Abstract: Substitution reactions Substitution reactions O 0040Nucleophilic Acyl Substitutions of Anhydrides with Protic Nucleophiles Catalyzed by Amphoteric, Oxomolybdenum Species. -A mild and efficient approach to a wide range of esters, amides, and thioesters starting from anhydrides is developed. Various substrates including cyclic and mixed ones react successfully as well as chemoselectively. -(CHEN*, C.-T.; KUO, J.-H.; PAWAR, V. D.; MUNOT, Y. S.; WENG, S.-S.; KU, C.-H.; LIU, C.-Y.; J.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2012
2012
2012
2012

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 27 publications
(54 reference statements)
0
2
0
Order By: Relevance
“…Chen and co-workers have demonstrated that the oxo-molybdenum complexes MoO 2 Cl 2 (1) and MoOCl 4 (118) are very efficient catalysts for the construction of C-O, C-N, and C-S bonds by nucleophilic acyl substitution (NAS) of anhydrides with a myriad array of alcohols, amines, and thiols, affording the corresponding acylated derivatives in high yields and high chemoselectivity (Fig. 47) [36]. Besides acetic anhydride, the catalytic system is amenable to a diverse array of cyclic and acyclic, aliphatic and aromatic anhydrides.…”
Section: Synthesis Of Esters Amides and Thioestersmentioning
confidence: 98%
“…Chen and co-workers have demonstrated that the oxo-molybdenum complexes MoO 2 Cl 2 (1) and MoOCl 4 (118) are very efficient catalysts for the construction of C-O, C-N, and C-S bonds by nucleophilic acyl substitution (NAS) of anhydrides with a myriad array of alcohols, amines, and thiols, affording the corresponding acylated derivatives in high yields and high chemoselectivity (Fig. 47) [36]. Besides acetic anhydride, the catalytic system is amenable to a diverse array of cyclic and acyclic, aliphatic and aromatic anhydrides.…”
Section: Synthesis Of Esters Amides and Thioestersmentioning
confidence: 98%
“…Conjugate addition of 17 to methyl acrylate led to 19. acetylation with acetic anhydride catalyzed by MoCl 2 O 2 converted the trityl alcohols 18, 19, and 8 to the corresponding PPG reagents 20, 21, and 22, respectively. 10 The neutral protecting group installation protocol developed in our laboratory 7 was successfully generalized to the new reagents. Thus, without using any other chemical reagents, heating the trityl acetates and an alcohol R′OH at 120 °C resulted in 7, 11, and 12, respectively.…”
mentioning
confidence: 99%